Teacher Leadership in English Language Teaching: Perspectives of Pakistani Undergraduate Students - Mansoor, Hafiza Sana; Sumardjoko, Bambang; Sutopo, Anam; Prayitno, Harun Joko; ., Sutama; Khan, Abdul Bari; Rahmawati, Laili Etika (Journal of Ecohumanism, 2024)
Teacher leadership has received increased attention as it develops teachers’ professionalism and enhances students’ learning. Traditionally, studies on teacher leadership have primarily emphasized administrative aspects. The aim of this study was to employ Full-Range Leadership (FRL) to explore teacher leadership in English Language Teaching (ELT) from the perspective of students at university level in Pakistan. A sample of fifteen students was selected through a convenience sampling technique from a private university in Multan city. This qualitative study conducted semi-structured interviews of students to enable content analysis of the data. All participants were contemporarily enrolled in undergraduate program in the Department of English. English language teachers possessed all three leadership aspects of the FRL model—transformational, transactional, and laissez-faire—as shown in the results. The findings revealed that English teachers were generally disciplined, dedicated, and organized, showing a stronger inclination toward the active components of the transactional and transformational leadership in the FRL model. Conversely, English teachers who were perceived as less effective in their interactions with students and teaching practices exhibited higher laissez-faire and passive transactional tendencies. This study suggests that integrating transformational and active transactional leadership in ELT can enhance student achievement and improve teacher-student relationships as these contribute to effective leadership.